Adaptation of Ritchie's Method for Parasites Diagnosing with Minimization of Chemical Products. (13th August 2012) - Anécimo, Régis Silva; Tonani, Karina A. A.; Fregonesi, Brisa Maria; Mariano, Ana Paula; Ferrassino, Marinês D. B.; Trevilato, Tânia M. B.; Rodrigues, Roberta Braga; Segura-Muñoz, Susana I.
Abstract : Latin America, Africa, and Asia present wide dissemination and high prevalence rates of waterborne parasitic diseases, which is a strong indicative of the fragility of public sanitation systems. In this context, parasitological analyses represent extremely relevant instruments. Several parasite diagnosis methods exist, among which Ritchie's method (1948) stands out. This method uses formaldehyde and ether, two reagents of toxicological importance that can cause damages to environmental and occupational health. The present study aimed to compare Ritchie's method modified by Régis Anécimo, without use of solvents, with the traditional Ritchie's method, routinely used for helminth and protozoa diagnosing in Brazil. Some changes were introduced in the modified method, such as controlled increase of water temperature used after stool dilution and substitution of formaldehyde and ether by a neutral detergent before material centrifugation for observation of parasites. In examined samples by both methods, multiple infections were commonly observed; the modified method presented a similar sensitivity to identify the parasites. The development of analytic diagnosis methods that minimize the use of chemical products like ether and formaldehyde represents an important tool to prevent occupational diseases among exposed professionals, as well as to preserve environmental quality through the use of clean techniques.